Berpikir strategis : Rencanakan masa depan dan wujudkan / Andy Bruce, Ken Langdom ; penerjemah Marina Sofyan ; editor Niken Hananti, Daniel P. Purba. - BRUCE, Andy; Ken Langdom; Marina Sofyan; Niken Hananti; Daniel P. Purba (Erlangga, 2009)
118 hlm. : ilus. ; 19 cm [3 eks.]